Thermal Dependence of the Threshold Current in Quantum Well Semiconductor Lasers - Sánchez, M.; Suárez Rojas, N.; Martin, J. A.; Mon, Elis (Revista Cubana de Física; Vol 26 No 1 (2009): Cuban Nanotechnology 2009, 2009)
Results on the temperature dependence of the threshold current density for semiconductor lasers based in different materials are presented, emphasizing in GaInNAs devices. In this case the model considers, the radiative, monomolecular and Auger recombination components. The monomolecular recombination coefficient (Am) was taken independent of temperature; while the radiative coefficient (Br ) was taken as Br ≈ T-1 and for Auger coefficient (CA) an exponential dependence was considered. These coefficients were used as adjustable parameters in the simulation. Results shown that while the monomolecular recombination is the main mechanism responsible for the increment of the threshold current with temperature the Auger component should be considered in all cases although with different weight related with the structure.